1995
DOI: 10.1152/ajpendo.1995.268.1.e1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on uric acid excretion in humans

Abstract: Although hyperuricemia is a frequent finding in insulin-resistant states, insulin's effect on renal uric acid (UA) handling is not known. In 20 healthy volunteers, diastolic blood pressure, body weight, and fasting plasma insulin were positively (and age was negatively) related to fasting plasma UA concentrations, together accounting for 53% of their variability. During an insulin clamp, urine flow was lower than during fasting conditions (1.01 +/- 0.12 vs. 1.56 +/- 0.32 ml/min, P = 0.04), whereas creatinine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(216 citation statements)
references
References 24 publications
4
199
2
4
Order By: Relevance
“…5 Previous work in the NAS and by others has found that hyperinsulinemia and elements of the metabolic syndrome are associated with the SUA level. [23][24][25] Insulin is known to decrease the renal excretion of uric acid, 4 and hyperinsulinemia predicts the development of hypertension. 26 We do not have serum insulin levels available at the baseline examination; however, the work of Imazu et al 12 suggests that the relationship between uric acid and the development of hypertension is independent of the insulin level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Previous work in the NAS and by others has found that hyperinsulinemia and elements of the metabolic syndrome are associated with the SUA level. [23][24][25] Insulin is known to decrease the renal excretion of uric acid, 4 and hyperinsulinemia predicts the development of hypertension. 26 We do not have serum insulin levels available at the baseline examination; however, the work of Imazu et al 12 suggests that the relationship between uric acid and the development of hypertension is independent of the insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia secondary to insulin resistance may also contribute to the association of hyperuricemia with hypertension. 4,5 Recent observations in experimental hyperuricemia suggest that uric acid may in fact have a pathogenic role in hypertension. 6 Hyperuricemia induces hypertension in experimental animals that corrects with hypouricemic therapy.…”
mentioning
confidence: 99%
“…One potential explanation is that hyperinsulinemia may cause hyperuricemia. For example, insulin acts on the proximal tubule to stimulate urate reabsorption coupled with sodium [32]. Fasting insulin levels inversely correlate with urinary uric acid clearance and are positively associated with serum uric acid in healthy subjects [28].…”
Section: Metabolic Syndrome Renal Disease and Uric Acidmentioning
confidence: 99%
“…There are various hypotheses as to why obesity causes hyperuricemia: for instance, accelerated uric acid production coupled with the synthesis of triglyceride (10), underexcretion of uric acid into the urine caused by the effect of insulin on the urinary tubular tract (11)(12)(13).…”
Section: Many Previous Reports Have Shown the Relationship Between Obmentioning
confidence: 99%
“…4). (19) (12,13,21). It is known that uric acid and sodium have a co-transporter system in the kidney (22).…”
Section: F I G U R E 1 Re L a T I O N S H I P B E T We E N T H E S mentioning
confidence: 99%